Green Economy Implementation in Indonesia: Legal Frameworks, Policy Challenges, and Implications for Human Rights - Samimi, Fatima (Unisia, 2025)
This article examines the implementation of the green economy in Indonesia and analyzes its implications for human rights within the framework of sustainable development. It aims to assess how national green economy policies and initiatives align with human rights principles and to what extent they contribute to inclusive and equitable development. Using a qualitative normative legal research method, the study relies on an analysis of statutory regulations, government policies, international reports, and relevant legal and policy documents, interpreted through a human rights–based approach and sustainable development theory. The findings show that Indonesia has adopted a range of legal and policy instruments supporting the green economy, particularly in the areas of energy transition, carbon pricing, environmental protection, and green investment. These initiatives have the potential to promote key human rights, including the right to a healthy environment, the right to health, the right to development, access to decent work through green jobs, and increased public participation in environmental governance. However, the study also identifies significant challenges in implementation, such as weak law enforcement, limited institutional capacity, insufficient monitoring mechanisms, and uneven inclusion of vulnerable groups, including local communities, women, and indigenous peoples. The analysis suggests that without strong governance, transparency, and accountability, green economy policies risk reproducing social inequalities and undermining human rights objectives. The article concludes that while the green economy offers meaningful opportunities to advance human rights in Indonesia, its success depends on strengthening legal frameworks, ensuring effective implementation, and embedding human rights considerations at every stage of policy design and execution, thereby supporting a just and inclusive transition toward sustainable development.